Листування М.Грушевського з М.Марром (вступна стаття й публікація В.В.Тельвака) (Український історичний журнал, 2014)
Публікується листування Михайла Грушевського з відомим мовознавцем
Миколою Марром, котре зберігається у Санкт-Петербурзькому філіалі Архіву
Російської академії наук. Висвітлюються незнані контакти вчених у другій половині 1920-х рр., у чиїх листах обговорювалися проблеми, пов’язані зі співпрацею російського академіка у журналі «Україна», а також його сприяння в реалізації запроектованого М.Грушевським Інституту дослідження історії України при Академії наук СРСР. The article deals with the publication of the correspondence of Mykhailo Hrushevs’kyi
with the famous linguist Nikolai Marr, which is stored in St. Petersburg branch
office of the archive of Russian Academy of Sciences. The correspondence highlights
the unknown contacts of scientists in the 20s years of 20th century. In the letters the
problems related to the cooperation of Russian academic in the journal “Ukraine”
have been discussed and also his promotion in the realization of the Institute of
Study of the History of Ukraine at the Academy of Sciences of the USSR planned
by M.Hrushevs’kyi has been pointed out.